Drug utilization study of antimicrobial agents in patients of neonatal sepsis in neonatal intensive care unit at a tertiary care hospital in western part of India - Amin, Anand J.; Shah, Prashant C.; Asari, Pratik D.; Malam, Prakash; Kalkoti, Vinob; Behl, Archana B. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Neonatal sepsis is one of the major causes of death and morbidity among neonates in India; however, studies related to neonatal sepsis are somewhat in limited numbers. Furthermore, time to time sensitivity and efficacy of various antimicrobial agents (AMA) change which necessitates studies related to antimicrobial drug utilization in hospitals. The objective of present study was to evaluate the pattern of use of AMAs in neonatal sepsis at the neonatal intensive care unit (NICU) at a tertiary care hospital in western part of India. Methods: It was a prospective cross-sectional study conducted over a period of 6-month duration in NICU at tertiary care hospital. Data were collected and analyzed. Results: It has been observed that 57.67% patients were pre-term, 42.32% full term; 23.28% were of normal birth weight, 58.73% low birth weight and 15.34% were very low birth weight. In 48.7% of patients, two different antibiotics were prescribed while in 40.1% of patients three different antibiotics were prescribed. A total number of antibiotics prescribed were 499, per patient 2.78 antibiotics were prescribed. Amikacin was used in 73.01% cases while cefotaxime was used in 64.55% of cases. Piperacilin + tazobactam combination was used in 41.26% cases. In 50.9% cases, antibiotics were prescribed by generic name. Conclusion: Antibiotic resistance is increasing due to the irrational prescribing habits of physicians, leading to increasing morbidity, mortality and treatment costs. Therefore, the medical professionals as well as government personnel who are related to the health sector need to understand that antibiotics are precious and finite resources. The remedy of this situation requires that regular educational awareness programs should be conducted in hospitals at a regular basis.